Paradigma Pendidikan Islam dalam Kajian Gender Perspektif Riffat Hasan - Supardi, Adi (Asatiza: Jurnal Pendidikan, 2022)
This study aims to describe the paradigm of Islamic education in several gender studies in Riffat Hasan's perspective. The method used is a qualitative method with descriptive analysis. This study resulted in the finding that the paradigm of Islamic education thought by Riffat Hasan about the position and role of men and women has clear roots, proving that before Allah humans are functionally the same, namely to worship and benefit others, that's all. Riffat Hasan demanded several things which he thought were unfair and equal in the teachings of Islam which were branded by patriarchal people, he emphasized that Islam is very fair in this gender issue, it's just that the patriarchs always act victorious on their own behalf and in the name of religion in their attitude.